The formation of assimilation apparatus in common buckwheat (Fagopyrum esculentum Moench) - Jana KALINOVÁ; Jan MOUDRÝ (Acta Agriculturae Slovenica)
In the years 1998 – 2000 the field experiments with two buckwheat varieties (Emka (tetraploid), Hruszowska (diploid)), were performed. We followed the development of assimilatory apparatus during the vegetation period and the influence of nitrogen fertilization (50 kg.ha-1) and variety on its forming. The basic modifying component applied to the production of assimilatory apparatus is of course the weather in a given year along with the soil conditions. Nitrogen fertilization increases leaf size, prolongs the life of leaves and thereby the persistence of maximum leaf area on plant, and supports indeterminate growth of buckwheat, which exhibits production of new branches and inflorescences. Larger leaf area in dense growth is not enough photosynthetically active and inhibits pollination of flowers. Newly created flowers compete with one another for nutrients and final number of achenes per plant declines. Higher utilization of applied fertilization was observed at the tetraploid variety.